ANALYSIS OF THE BATANG LANGKUP RIVER DISCHARGE USING FLOATING METHOD FOR MICRO-HYDRO POWER PLANT NEEDS (PLTMH) - Siregar, Anggi Deliana; Chandra Kirana, Febiyora; Ritonga, D. M Magdalena; Tadersi, Risnaliyah Nuriil; Trianda, Obrin; Nugroho, Nanda Eko; Febriansanu, Dicko Rizky (JOURNAL ONLINE OF PHYSICS, 2025)
Water resources are renewable natural resources that have a volume with constant conditions in the hydrological cycle. The constant presence of water in the hydrological cycle can make water a source of energy. Water potential is also influenced by the presence of high rainfall in an area. The higher the rainfall, the higher the potential of water as a source of renewable energy, one of which is a micro-hydro power plant. The use of energy sources from hydropower has great potential in hilly complexes that have large river networks. To meet the need for electrical energy in the Rantau Kermas Village area, Jangkat District, Merangin Regency, Jambi Province, a water discharge calculation is needed to determine the estimated availability of energy. The calculation of water discharge in the Rantau Kermas Village Area, Jangkat District, Merangin Regency, Jambi Province was carried out using the floating method with the results obtained being 4,644 m3/s. and can increase or decrease depending on the rainy season or dry season. Water discharge value data can be used as information for the purposes of developing water resources as a Micro Hydro Power Plant (PLTMH) in the discharge